Effects of rivaroxaban on myocardial ischemia-reperfusion injury in rats - Ercan Kahraman; Baris Akca; Mehmet Cengiz Colak; Olcay Murat Disli; Hakan Parlakpinar; Bektas Battaloglu; Nevzat Erdil (Medicine Science, 2022)
Myocardial infarction and further ischemia-reperfusion injury is a life-threatening conditions in humans. In this study, the effects of rivaroxaban, an anticoagulant agent, were aimed to be studied in a myocardial ischemia-reperfusion (I/R) injury model in rats. Male Wistar-albino rats were allocated into three groups; Rivaroxaban (n=15), control (n=15) and sham (n=10). Myocardial ischemia (30 minutes) and then reperfusion (120 minutes) were surgically performed in the rivaroxaban given (3mg/kg/day by gavage for 10 days before surgical procedures) and the control groups. Electrocardiography changes, blood pressure and heart rate were recorded before ischemia, and during the periods of ischemia and the reperfusion. Hemodynamic and blood parameters were recorded. Necrotic tissue in the myocardium was determined by the triphenyl tetrazolium chloride dye method. The extent of myocardial necrosis and risk area was calculated using a computer-assisted image program. In the rivaroxaban administered group, the size of necrotic area in the myocardium decreased significantly, however, mean heart rate and mean arterial blood pressure did not change. K+ and CK levels in serum, which are indicative of tissue necrosis, were significantly lower in the rivaroxaban group compared to the control group (p [Med-Science 2022; 11(4.000): 1456-60]